Microsoft SQL Server 2005 notification services - Pather, Shyam (Sams, 2006)
Microsoft SQL Server 2005 Notification Services covers the basic problems of notification applications, describes the SQL Notification Services platform and describes how to use it to build rich, scalable notification applications. Written by Shyam Pather , the Technical Lead for the SQL Notification Services Team, this book is based on his three years of experience teaching SQL Notification Services to new customers. This book is your complete resource for learning SQL Notification Services application development and the underlying architectural concepts.